Efektivitas Pendampingan Kepemimpinan dalam Meningkatkan Kualitas Kedisiplinan Santri di Pesantren - Nurhaliza, Sabrina (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Leadership mentoring is an important strategy in improving the quality of student discipline in Islamic boarding schools, especially amidst the demands of modernization, social dynamics, the development of external social media, and the need to strengthen the character of students as future leaders. This PKM was carried out to analyze and test the effectiveness of leadership mentoring carried out through training for administrators and heads of rooms at the An-Nur II Putri Bululawang Islamic Boarding School, Malang. The focus of PKM was directed at how structured mentoring could improve discipline, strengthen internal coordination, and improve the quality of the pesantren's etiquette environment. Implementation methods included participatory observation, in-depth interviews, leadership training, familiarization with Islamic leadership values, and weekly training for administrators and heads of rooms. Mentoring was carried out with a leadership approach that included the functions of planning, organizing, directing, supervising, and focusing on handling to improve the quality of student discipline. From the results of the activities obtained, mentoring was able to increase awareness and capacity of student discipline, seen from increased discipline, successful program implementation, ability to lead small groups, accurate decision-making, ability to provide evaluations and communication skills in solving problems. In addition, student discipline in Islamic boarding schools has become more effective through better coordination, increased professionalism of administrators, ongoing evaluations, and the development of approaches to provide students with examples. This mentoring model, which combines exemplary behavior from caregivers, habituation, and technical training, can serve as an example for other Islamic boarding schools seeking to strengthen student discipline and build character that is noble and akhlaqul karimah (good character) both within the boarding school and after leaving.